Symposium 10: Infrastructures, institutions and networked learning - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2008)
Universities can be criticized for setting up walled gardens, areas cut away from the mainstream of technological change. It is also suggested that some technologies, specifically Web 2.0, are unable to be contained in this way and that they threaten to breach the walls that universities put in place. Much of this discussion can have a flavour of radical innovation, the university is portrayed as slow and cumbersome, whilst the new wave of technology is wild and spontaneous. This paper suggests that any such view misses some significant and recurrent features of social and educational practice. A core function of a university is to provide credentials and to stand behind those credentials by having warranted procedures. The university even in times of rapid technological change stands for a certain kind of institutional security and the waves of technological pressure may result in changes but these changes will be adapted, adopted and ameliorated by the active agency of university organizations engaging with the new technologies as co-creators not as simple recipients of technological imperatives. Web 2.0 technologies are currently identified as technologies that imply a different relationship between institutional boundaries and wider social forms. This paper investigates the use of the term infrastructure to understand these broad questions about the relationship between pervasive technologies and institutional forms. The concept is clarified in relation to the idea of infrastructure as something that fades into the background, only an infrastructure in so far as it is largely invisible. This is contrasted with a relational view of infrastructure which suggestes that infrastructures are only infrastructures in relation to social purposes. An infrastructure for learning for example would only become such when it was incorporated into learning practices. In this view infrastructures are not to be understood as simply structures because they are processes occurring over time. Infrastructures were also located within specific settings as work-oriented infrastructures and learning infrastructures. In terms of a learning infrastructure a case was made that we need to be cautious because learning infrastructures are often constituted from elements that are neither designed for nor assigned to learning as such, and an infrastructure for learning may incorporate aspects used for learning whilst not being particular identified with learning. The idea of learning infrastructure proposed here is a relational and socio-technical view: A learning infrastructure is a socio-technical arrangement over a period of time of technologies and artefacts intertwined with social and organisational practices that is enacted for the purpose of learning. This view of infrastructure is then illustrated by research focusing on the deployment of the Open University VLE. A large infrastructural project that developed and deployed a range of new technologies, including Blogs, wikis, an e-portfolio and an adaptive assessment system across the Open University. The Open University VLE programme illustrates some of the reasons why universities are likely to be reluctant to take down the walls around institutional provision of the learning infrastructure. Issues of security and equality alongside standard concerns about cost and uniformity inform the way technologies are both developed and deployed. There is no one authoritative voice in this process and whilst the process of infrastructural development and renewal can seem to be the outcome of a plan the process is one that is negotiated between powerful institutional interests that have their roots in different roles within the university. Negotiation is not only between units and the process of decision making is also affected by the sequence of time in terms of taking decisions, for example by who is in post when key decisions are taken. Decisions taken in terms of the technological solutions for infrastructural development have definite consequences in terms of the affordances and constraints that deployed technologies have in relation to local practices. The strengths and weaknesses of an infrastructure seem to reside in a complex interaction of time, artefacts and practices.